Effect of date of planting and spacing on grain yield and quality of scented rice (Oryza sativa) varieties in wet season in coastal Orissa - CHANDRA, DINESH; LODH, S B; SAHOO, K M; NANDA, B B (The Indian Journal of Agricultural Sciences, 2013)
Effect of planting date and spacing was studied in wet season with 12 Basmati rice (O,yza sativa L.) varieties at CuttackÂ Â Â Â in alluvial soils during 1991 and 1992 to find out their performance under 2 planting dates and spacings in relation to their yield and quality. The varieties were ’Basmati 370’, ’Kapurthala Basmati’, ’Ranbir Basmati’, ’Dehradun Basmati’, ’IET 11347’, ’IET 8579’, ’Pusa 615’, ’Gaurav’, ’CB II’, ’Dubraj’, ’Kalimuch’ and ’Madhuri’; the dates of planting were 25 July 1991,5 September 1991,25 July 1992 and 11 August 1992; and planting densities were 20 cm X 15 cm (33 hills/m2) and 15 cm X 15 cm (44 hills/m2 ). The scented rice varieties planted on 25 July gave significantly higher yields of rough rice than those planted late on 5 September 1991 (10%) or August 1992 (12%). When transplanted late, 4 out of 12 varieties gave higher yield, 5 gave lower yield and 3 gave similar yield. States like West Bengal and Orissa also produce scented rice during the wet season, giving reasonably good yields when compared with 3.5-4.0 tonnes/ha obtained from the traditionally scented-rice areas. The highest head-rice recovery was obtained from ’Dubraj’ (61.48%) and the lowest with ’CB II’ (32.9%). Late-planted crop (11 August) gave higher head-rice recovery than early-planted rice (25 July) during 1992.